Eosinophilic fasciitis associated with hypereosinophilia, abnormal bone‐marrow karyotype and inversion of chromosome 5. (16th November 2013) - Ferguson, J. S.; Bosworth, J.; Min, T.; Mercieca, J.; Holden, C. A.
Summary We report the case of a male patient presenting with eosinophilia, pulmonary oedema and eosinophilic fasciitis (EF). He had the classic clinical appearance and magnetic resonance imaging of EF. Cytogenetic analysis of the bone marrow revealed a previously undescribed pericentric inversion of chromosome 5. Overall, the presentation was consistent with a diagnosis of chronic eosinophilic leukaemia, not otherwise specified (CEL‐NOS). Dermatologists should consult a haematologist in cases of EF, in order to rule out possible haematological malignancies.